1969
DOI: 10.1002/jsfa.2740200909
|View full text |Cite
|
Sign up to set email alerts
|

Effect of storage temperature on the ageing of concentrated wheat starch gels

Abstract: Using differential thermal analysis (d.t.a.) the progress of ageing of concentrated wheat starch gels stored at temperatures from -l o to 43" has been investigated.A very close relationship has been found between the ageing of starch gels as measured by d.t.a. and the staling of bread as measured by crumb firmness at storage temperatures of -lo, 10" and 21" but some differences have been found at 32" and 43". The results at -lo, 10" and 21" provide very strong confirmatory evidence that starch crystallisation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
30
1
1

Year Published

1984
1984
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(35 citation statements)
references
References 3 publications
3
30
1
1
Order By: Relevance
“…The melting temperature of crystallised amylopectin increases with increasing storage temperature, indicating that more stable crystals are formed at higher storage temperatures. The storage temperature used in most experiments ( + 7°C) was chosen to give good conditions for crystallisation of amylopectin (Colwell et al 1969). The results obtained in the present work clearly show that the addition of a surfactant such as CTAB greatly reduces the rate of crystallisation during these conditions, the effect of the added surfactant being greater at + 25°C than at + 7°C (Fig 3).…”
Section: Discussionsupporting
confidence: 60%
“…The melting temperature of crystallised amylopectin increases with increasing storage temperature, indicating that more stable crystals are formed at higher storage temperatures. The storage temperature used in most experiments ( + 7°C) was chosen to give good conditions for crystallisation of amylopectin (Colwell et al 1969). The results obtained in the present work clearly show that the addition of a surfactant such as CTAB greatly reduces the rate of crystallisation during these conditions, the effect of the added surfactant being greater at + 25°C than at + 7°C (Fig 3).…”
Section: Discussionsupporting
confidence: 60%
“…Thus, nucleation rate increases with decrease in temperature down to Tg while the propagation rate increases with increasing temperature up to the Tm (Wunderlich, 1976). Several studies ' (Colwell et al, 1969;Fearn, & Russell, 1982;Jankowski, & Rha, 1986) have shown that the rate limiting step for starch retrogradation is nucleation and the rate of retrogradation as well as the properties ofretrograded starch gel depend on the storage temperature (Jankowski, & Rha, 1986 …”
Section: Storage Temperaturementioning
confidence: 99%
“…7 Colwell et al were the first to investigate the aging of wheat starch gels by differential thermal analysis. 8 Other techniques used are: differential scanning calorimetry (DSC), 9 -12 nuclear magnetic resonance, 13 rheometry, 14 microscopy, 7 Raman, 15 and infra-red spectroscopy. 16 Silverio et al used isothermal microcalorimetry to follow the crystallization of starch.…”
Section: Introductionmentioning
confidence: 99%